Association between Caesarean Delivery and Childhood Asthma in India and Vietnam. Issue 1 (6th November 2016) - Lavin, Tina; Franklin, Peter; Preen, David B.
Abstract: Background: While there is evidence of an association between caesarean birth and increased asthma in children in high‐income countries, it is unknown whether this association exists in low‐to‐middle‐income countries (LMICs). We investigated whether children born through caesarean in India and Vietnam are at increased risk of caregiver‐reported asthma by 8 years of age. Methods: Data from an ongoing multi‐national longitudinal cohort study (the Young Lives Study) in two LMICs (India n = 2026; Vietnam n = 2000) were used. Caregiver questionnaires captured information on caregiver‐reported long‐term respiratory problems such as asthma or wheeze at age 8 years, birth mode and a range of sociodemographic factors. Multivariable logistic regression models using propensity score adjustment were used to explore birth mode and asthma at age 8 years adjusted for a range of known confounders. Results: Children delivered by caesarean in India (odds ratio (OR) 2.6, 95% confidence interval (CI) 1.3, 5.4) and Vietnam (OR 2.0, 95% CI 1.2, 3.3) had greater odds of asthma at age 8 years, after adjustment for other risk factors including wealth, liveborn parity, low birthweight, geographic location, cooking fuel used, livestock ownership, household size, housing quality and parental smoking. Conclusions: The study suggests that caesarean birth may be associated with an increased risk of childhood asthma in India and Vietnam. The underlying mechanisms of this finding need to be further elucidated.